2020
DOI: 10.1182/bloodadvances.2019001381
|View full text |Cite
|
Sign up to set email alerts
|

Real-world outcomes of adult B-cell acute lymphocytic leukemia patients treated with blinatumomab

Abstract: The availability and use of blinatumomab symbolizes a paradigm shift in the management of B-cell acute lymphoblastic leukemia (ALL). We conducted a retrospective multicenter cohort analysis of 239 ALL patients (227 relapsed refractory [RR], n = 227; minimal residual disease [MRD], n = 12) who received blinatumomab outside of clinical trials to evaluate safety and efficacy in the “real-world” setting. The median age of patients at blinatumomab initiation was 48 years (range, 18-85). Sixty-one (26%) patients had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 24 publications
(33 reference statements)
2
24
1
Order By: Relevance
“…Blinatumomab therapy has demonstrated encouraging activity in patients with relapsed/refractory (r/r) and minimal residual disease-positive (MRD+) B-cell acute lymphoblastic leukemia (B-ALL). [1][2][3][4][5] Among patients with r/r B-ALL, disease relapse is common in blinatumomab responders, 6 and blinatumomab is often used as a bridging therapy toward curative allogeneic hematopoietic cell transplantation (HCT). Recently published outcomes of a post hoc analysis of the phase II confirmatory study suggest blinatumomab as a potential curative treatment without allogenic HCT in a subset of patients who achieve a complete MRD response.…”
Section: Introductionmentioning
confidence: 99%
“…Blinatumomab therapy has demonstrated encouraging activity in patients with relapsed/refractory (r/r) and minimal residual disease-positive (MRD+) B-cell acute lymphoblastic leukemia (B-ALL). [1][2][3][4][5] Among patients with r/r B-ALL, disease relapse is common in blinatumomab responders, 6 and blinatumomab is often used as a bridging therapy toward curative allogeneic hematopoietic cell transplantation (HCT). Recently published outcomes of a post hoc analysis of the phase II confirmatory study suggest blinatumomab as a potential curative treatment without allogenic HCT in a subset of patients who achieve a complete MRD response.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, most R/R B-ALL patients are unlikely to respond very well to blinatumomab treatment. Besides, it was reported that a substantial portion of R/R B-ALL patients with a history of or concurrent extramedullary disease failed to respond to blinatumomab, indicating the poor ability of blinatumomab in treating extramedullary disease 18 , 19 . To improve the treatment efficacy of blinatumomab, we proposed to apply the adoptive transfer of ex vivo expanded γδ T cells to supplement functional T cells in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Inotuzumab mAb2 was an effective salvage therapy for patients who relapsed after blinatumomab mAb1 irrespective of CD19 expression or receipt of other interim salvage therapy between mAb1 and mAb2. The CR rate following inotuzumab mAb2 treatment was 68%, comparable to CR rates observed with inotuzumab when used in salvage 1 and 2 and blinatumomab naïve setting (18)(19)(20). Inotuzumab also yielded comparable responses whether it was used immediately following blinatumomab or after interim salvage therapy following post-blinatumomab.…”
Section: Discussionmentioning
confidence: 54%